Predictive role of arterial lactate in acute kidney injury associated with off-pump coronary artery bypass grafting - Yu, Ruiming; Liang, Tingyi; Li, Longfei; Bi, Yanwen; Meng, Xiangbin (Frontiers in Surgery, 2023)
Objectives: This observational study aims to explore the predictive role of postoperative arterial lactate in off-pump coronary artery bypass grafting (CABG)-associated acute kidney injury (AKI). Materials and Methods: A total of 500 consecutive patients who underwent off-pump CABG from August 2020 to August 2021 at the Department of Cardiovascular Surgery, Qilu Hospital of Shandong University, were included. Logistic regression analysis was used to confirm the independent risk factors of off-pump CABG-associated AKI. Receiver operating characteristic (ROC) curve was performed to evaluate the discrimination ability and Hosmer–Lemeshow goodness of fit test was performed to evaluate the calibration ability. Results: The incidence of off-pump CABG-associated AKI was 20.6%. Female gender, preoperative albumin, baseline serum creatinine, 12-h postoperative arterial lactate and duration of mechanical ventilation were independent risk factors. The area under the ROC curve (AUC) of 12-h postoperative arterial lactate for predicting off-pump CABG-associated AKI was 0.756 and the cutoff value was 1.85. The prediction model that incorporated independent risk factors showed reliable predictive ability (AUC=0.846). Total hospital stay, intensive care unit stay, occurrence of other postoperative complications, and 28-day mortality were all significantly higher in AKI group compared to non-AKI group. Conclusion: 12-h postoperative arterial lactate was a validated predictive biomarker for off-pump CABG-associated AKI. We constructed a predictive model that facilitates the early recognition and management of off-pump CABG-associated AKI.